2018
DOI: 10.1002/bmc.4253
|View full text |Cite
|
Sign up to set email alerts
|

Determination of four antiepileptic drugs in plasma using ultra‐performance liquid chromatography with mass detection technique

Abstract: Status epilepticus (SE) is considered the second most frequent neurological emergency. Its therapeutic management is performed using sequential antiepileptic drug regimens. Diazepam (DIA), midazolam (MID), phenytoin (PHT) and phenobarbital (PB) are four drugs of different classes used sequentially in the management of SE. A sensitive, selective, accurate and precise method was developed and validated for simultaneous determination of the four antiepileptic drugs in human plasma. Their separation and quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…17 Another detailed definition was given by the Epilepsy Foundation of America specifying a condition, where two or more consecutive seizures happen with loss of consciousness between them, or a persistent seizure that lasts for more than 30 minutes, as status epilepticus (SE). 18 The WHO states that epilepsy causes a major public health concern because it is an important cause for mortality and morbidity around the world. Also, population-based studies show that SE is considered the second most frequent neurologic emergency associated with high annual occurrence that increases almost logarithmically with age.…”
Section: Carbamazepine As An Effective Antiepileptic Drug (Aed)mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Another detailed definition was given by the Epilepsy Foundation of America specifying a condition, where two or more consecutive seizures happen with loss of consciousness between them, or a persistent seizure that lasts for more than 30 minutes, as status epilepticus (SE). 18 The WHO states that epilepsy causes a major public health concern because it is an important cause for mortality and morbidity around the world. Also, population-based studies show that SE is considered the second most frequent neurologic emergency associated with high annual occurrence that increases almost logarithmically with age.…”
Section: Carbamazepine As An Effective Antiepileptic Drug (Aed)mentioning
confidence: 99%
“…Also, population-based studies show that SE is considered the second most frequent neurologic emergency associated with high annual occurrence that increases almost logarithmically with age. 18,19 Prevalence studies of neurological disorders showed high rates of epilepsy in Arab countries including Egypt, Saudi Arabia and Lebanon, yet very few published studies evaluate the situation in these countries.…”
Section: Carbamazepine As An Effective Antiepileptic Drug (Aed)mentioning
confidence: 99%